Energy decay for a viscoelastic wave equation with space-time potential in Rn (2022)
In this paper, we consider the following viscoelastic wave equation with space-time dependent potential and where the initial data u0(x), u1(x)have compact support. Under suitable assumptions on the relaxation function g and the potential b, we obtain a more general energy decay result using the perturbed energy method.